Konsentrasi dan Kualitas Spermatozoa Kucing Domestik (Felis catus) yang diambil dari Epididymis dan Ductus deferens setelah Preservasi pada Suhu 4oC - Supriatna, Iman; Agungpriyono, Srihadi; Boediono, Arief; Nazlie (Alm), Cutnya’ Shaliran (Universitas Atma Jaya Yogyakarta, 2006)
The aim of this study was to evaluate the concentration, progressively motile, and percent live sperm in the various regions of epididymis and ductus deferens after preservation at 4oC. Epididymis and ductus deferens were collected from 21 epididymis and ductus deferens of domesticated cat (Felis catus) by castration. One testicle of pair (control testicle) was analyzed at the day of castration, while the other testicle of the pair was stored at 4oC up to 7 days. The sperm concentration, percentage of sperm motility and live sperm were examined daily until day-7 of preservation. The sperm concentration was higher (p<0.05) in cauda epididymis (23.99x106 sperm/ml) and ductus deferens (25.42x106 sperm/ml) than caput (11.51x106 sperm/ml) and corpus epididymis (14.82x106 sperm/ml). The percentage of sperm motility and live sperm decreased (p<0.05) during preservation period. However, the percentage of motile (11.33 to 16.00 %) and live (15.05 to 20.20 %) sperm could be found in preserved epididymis and ductus deferens up to day-7. These results show that motile and live sperm can be collected from cat’s epididymis and ductus deferens up to day 7 after preservation at 4oC.